Nontuberculous Mycobacteria as Sapronoses: A Review - Pavlik, Ivo; Ulmann, Vit; Hubelova, Dana; Weston, Ross Tim (Microorganisms, 2022)
Mycobacteria are a unique group of microorganisms. They are characterised by exceptional adaptability and durability. They are capable of colonisation and survival even in very unfavourable conditions. In addition to the well-known obligate human pathogens, Mycobacterium tuberculosis and M. leprae, more than 200 other species have been described. Most of them form a natural part of the microflora of the external environment and thrive in aquatic and soil environments especially. For many of the mycobacterial species associated with human disease, their natural source has not yet been identified. From an ecological point of view, mycobacteria are saprophytes, and their application in human and animal diseases is opportunistic. Most cases of human disease from saprophytic mycobacteria occur in immunocompromised individuals. This adaptability and resilience to environmental pressures makes treatment of mycobacterial diseases (most often sapronoses and less often zoonoses) and permanent eradication of mycobacteria from the environment very difficult. Saprophytic mycobacterial diseases (sapronoses) are chronic and recurrent due to the fact of repeated endogenous or exogenous re-exposure. Therefore, knowledge regarding their occurrence in soil and dust would aid in the prevention of saprophytic mycobacterioses. In conjunction, their presence and ecological significance in the environment can be revealed.
Keywords: trace elements deficiency; environmental saprophytic mycobacteria; saprophytic mycobacteria; soil exposure; earth-eating; mud; potentially pathogenic mycobacteria; soil consumption; saprozoic mycobacteria; geochemistry; feeding and eating disorders; geophagia; PICA practices; antidiarrheal